Hierarchical sliding mode control for an underactuated mimo system - Nguyen, Van Dong Hai; Huynh, Xuan Dung; Nguyen, Minh Tam; Mircea Ivanescu,; Mircea Nitulescu, (Journal of Technical Education Science, 2018)
The paper proposed a balancing control for MIMO under-actuated systems. In this paper, human walking robots, the athlete robot, are researched. The dynamic equations of this model are generated by Euler Lagrange method. The balancing control on the stance phase is studied. Balancing on one leg is a basic behavior of athlete in order to developing other behavior controlling. The hierarchical sliding mode control algorithm is proposed. Numerical simulations show the method efficiency and robustness